KOMUNITAS LEPIDOPTERA DAN PARASITOIDNYA PADA PERTANAMAN MENTIMUN DI BOGOR, SUKABUMI DAN CIANJUR, JAWA BARAT - Ulina, Evawaty S.; Rizali, Akhmad; ., Pudjianto; Manuwoto, Sjafrida; Buchori, Damayanti (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2016)
Lepidopteran community and its parasitoid on cucumber field in Bogor, Sukabumi and Cianjur District, West Java. Cucumber is one of horticultural commodities that are widely cultivated in Indonesia, but information related to Lepidoptera pests and their parasitoids are limited. The aim of this study was to obtain information about Lepidopteran community on cucumber and their parasitoid diversity. Lepidopteran larvae were collected from 16 cucumber sites in the District of Bogor, Sukabumi and Cianjur in November 2014 until May 2015. Larvae were collected from each cucumber plant follow along 60 m transects. Larvae were collected from the field then brought to the laboratory. All larvae were then reared on cucumber leaves until pupation and parasitoids emerged. The data obtained were tested by analysis of the mean and analysis of variance (One way ANOVA) using the program R Stat. The results showed that cucumber plants were attacked by six species (morphospecies) belonging to four families of Lepidoptera. Diaphania indica (Saunders) (Lepidoptera: Crambidae) is the most abundant species found. All species (morphospecies) of Lepidoptera are more common when the cucumber plants are in the generative growth stage. Our result further showed that D. indica was attacked by 9 parasitoid larvae and 3 parasitoid pupae, C. chalcites (Lepidoptera: Noctuidae) by 5 parasitoids dan S. litura (Lepidoptera: Noctuidae) by 2 parasitoids. A braconid, Apanteles taragamae, is the most common parasitoid of D. indica found in the field. Its parasitism rate can reach 27% in the field. Overall, this research revealed that a number of parasitoids, that were found attacking Lepidopteran on cucumber indicates their potential use as biological control agents in this agroecosystems.